Malnutrition Essentials for Neurologists and Neurosurgeons: A Review of the Literature - Tahta, Alican; Turgut, Yasar B.; Sahin, Cem (Journal of Pediatric Neurology, 2021)
Malnutrition still causes deaths in the world today and protein energy malnutrition (PEM) is characterized by increased oxidative stress, immune deficiency, and development of various infections. Even today, however, it is an underrecognized and undertreated entity in neurology and neurosurgery. In this article, we therefore seek to review the available literature regarding various factors affecting surgical outcome of children with malnutrition undergoing some neurosurgical interventions including shunt surgery and traumatic brain injury in intensive care unit, in addition to its effects upon oxidative stress status and immunity. Furthermore, we attempt to provide essential knowledge of malnutrition affecting surgical outcome of patients with PEM. Based on available evidence in the published literature, it is concluded that it is a serious public health problem characterized by increased oxidative stress, immune deficiency, and development of various infections.
Keywords: immunity; infection; oxidative stress; outcome; protein energy malnutrition; surgery